Pengisian Baterai Ion Litium dengan Variasi Arus Menggunakan Modul TP4056 dan TP5100 - Refly, Septia; Putra, Gandhi Rizky Mahendro; Kusuma, Hollanda Arief (Newton-Maxwell Journal of Physics, 2025)
The charging speed of lithium-ion batteries depends on the applied current, with higher currents resulting in faster charging.  However, higher currents can increase the surface temperature, potentially damaging components or causing safety hazards. This study measured the surface temperature of lithium-ion batteries using the DS18B20 sensor. The TP4056 module was used for currents of 880.9 mA, 982.30 mA, and 1134.40 mA, while the TP5100 module was used for a current of 1323.80 mA. Charging at 1328.38 mA required the shortest time, approximately 3-4 hours. Temperature measurements showed no significant increase across the range of 880.0-1328.38 mA. For 982.30 mA, the first and second measurements recorded maximum temperatures of 34.4 °C and 36.2 °C, respectively. In the third measurement at 1328.38 mA, the maximum temperature reached 35.5 °C. Overall, the temperature variations remained below the maximum safe limit for lithium-ion battery charging.